Skrining Farmakognosi Tanaman Etnofarmasi Asal Kabupaten Bulukumba yang Berpotensi sebagai Antikanker - Asni Amin (Journal of Tropical Pharmacy and Chemistry, 2012)
The use of traditional medicine has long been known and used by the people of South Sulawesi and recorded since the 15th century in lontara 'pabbura. Bulukumba as one of the areas of south Sulawesi inhabited by ethnic of Kajang and ethnic of Makassar has also been used plants to treat several of diseases including. Screening studies pharmacognostic origin Bulukumba conducted to identify medicinal plants used by the community Bulukumba to treat cancer. The research location is the village of Bahari Bonto Lembanna District Bulukumba, The research location is the village Lembana of Bonto Bahari District Regency of Bulukumba, the surveys plants etnofarmasi through sanro (traditional healers), public figures and society who have knowledge of traditional medicine with purposive sampling method. Pharmacognosy screening includes determination etnofarmasi plants that have been collected, organoleptic examination, morphology, anatomy and identification of chemical constituents using color reagent and precipitation reactions. The results obtained five plants etnofarmasi potential for the treatment of cancer, leaf of landep (Barleria prionitis L.) Family Acanthaceae, gewor (Basella rubra L) Famili Acanhtaceae, pecut kuda (Stachytarpheta jamaicensis) Family Loranthaceae, rumput mutiara (Hedyotis corymbosa L.) family Rubiaceae dan gondola (Commelina benghalensis L.) Family Commelinaceae, with chemical ingredients contain flavonoids, saponins, alkaloids, and tannins. The content of flavonoids and alkaloids in plants has the potential to be used as a cancer treatment. Keywords : Etnopharmacy, anticancer, Pharmacognosy screening. Abstrak Penggunaan obat tradisional telah lama dikenal dan digunakan oleh masyarakat Sulawesi Selatan dan dibukukan sejak abad ke-15 dalam lontara’ pabbura. Bulukumba sebagai salah satu wilayah Sulawesi Selatan dihuni oleh etnis Makassar dan etnis Kajang juga telah menggunakan tanaman termasuk untuk mengobati berbagai penyakit. Penelitian skrining farmakognostik asal Kabupaten Bulukumba dilakukan dengan tujuan untuk mengidentifikasi tanaman obat yang digunakan oleh masyarakat Bulukumba untuk mengobati penyakit kanker. Lokasi penelitian adalah desa Lembanna Kecamatan Bonto Bahari Kabupaten Bulukumba, dengan mensurvei tanaman etnofarmasi melalui sanro (pengobat tradisional), tokoh masyarakat dan masyarakat yang memiliki pengetahuan tentang obat tradisional dengan metode purposive sampling. Skrining farmakognosi meliputi determinasi tanaman etnofarmasi yang telah dikumpulkan, pemeriksaan organoleptik, morfologi, anatomi dan identifikasi kandungan kimia menggunakan pereaksi warna dan reaksi pengendapan. Hasil penelitian didapatkan lima tanaman etnofarmasi yang potensial untuk pengobatan kanker yaitu daun landep (Barleria prionitis L.) Famili Acanthaceae, gewor (Basella rubra L) Famili Acanhtaceae, pecut kuda (Stachytarpheta jamaicensis) Famili Loranthaceae, rumput mutiara (Hedyotis corymbosa L.) family Rubiaceae dan gondola (Commelina benghalensis L.) famili Commelinaceae, dengan kandungan kimia mengandung flavanoid, saponin, alkaloid, dan tanin. Kandungan flavonoid, dan alkaloid dalam tanaman berpotensi untuk digunakan sebagai obat kanker. Kata Kunci : Etnofarmasi, Antikanker, Skrining farmakognosi.